Decentering Otherness: Intercultural Encounters and Ethical Imperatives in Kuessipan - Pribiag, Ioana (Nouvelles vues)

(untitled) (Observatoire du cinéma au Québec, 2022)
An emerging First Nations cinema in Québec is progressively challenging both exotic or naïve representations of “the Indigenous Other” on the one hand, and falsely homogenous representations of a Québécois identity on the other. Kuessipan (2019), Myriam Verreault and Naomi Fontaine’s collaborative adaptation of Fontaine’s eponymous novel, is one of the most highly acclaimed productions within this shifting cinematic landscape. This article examines the ethical implications of the film’s narrative, form and production process as modes of intercultural encounter. It claims that by opening a space of productive exchange and solidarity—within the film, in its interpellation of viewers, and through Verreault and Fontaine’s engagements with each other and the public—Kuessipan is emblematic of the ethical ideals of “cinéma-monde” (Gott and Schilt).